Pengaruh Komunikasi dan Teamwork (Kerjasama Tim) terhadap Kinerja SDM Pelayanan pada Rumah Sakit Umum Daerah (RSUD) H. Abdul Manap Kota Jambi - Ferzi, Noviardi; Luthfi, Musthafa; Albetris, Albetris; Sumantri, Sumantri (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the effect of communication and teamwork on the performance of human resources (HR) in service at the H. Abdul Manap Regional General Hospital (RSUD) in Jambi City. This study used a quantitative approach with an associative approach. The population consisted of 443 HR personnel, with purposive sampling based on specific criteria. The data collection instrument was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The results showed that communication and teamwork significantly influenced HR performance, contributing 32%. Partially, communication and teamwork also significantly influenced HR performance. These findings emphasize the importance of effective communication and teamwork in supporting the improvement of healthcare worker performance in hospitals.